The Effects of Replacing Dicalcium Phosphate with Busumbu Rock Phosphate on Performance and the Mechanical Properties of Bone in Growing Chicks - Odongo, N.E.; Plazier, J.; Straaten, P. van; McBride, B. (Springer, 2002)
Three hundred, day-old broiler chicks, with an average initial weight of 41.8±1.79 g, were used in a 15-day study (10 birds per battery cage) to characterize their performance and fluorine status when dicalcium phosphate (DCP) was replaced by Busumbu rock phosphate (BRP) as the source of phosphorus in the chicks' ration. The treatments comprised a standard ration with BRP replacing 0, 25%, 50%, 75% or 100% of DCP. Replacing DCP with BRP significantly reduced the final weight of the chicks (p<0.01), feed intake (p<0.01), weight gains (p<0.01) and dry matter digestibility (p<0.05) but increased (p<0.05) the feed-to-gain ratio. True phosphorus absorption and the percentage of phosphorus in the tibia were not affected by increasing amounts of BRP in the diet. Increasing levels of BRP in the diet linearly reduced (p<0.01) the percentage bone ash, calcium, Ca:P ratio, ultimate breaking force, bending moment, stress, and modulus of elasticity. Leg stiffness, lameness, reduced feed intake, and a decline in general health were recorded in 10–40% of the chicks on 75% and 100% BRP, respectively. These results suggest that excessive ingestion of fluorine from the BRP caused the reduction in the chicks' performance.